SiO2 Antireflection Coatings Fabricated by Electron-Beam Evaporation for Black Monocrystalline Silicon Solar Cells - Minghua Li; Hui Shen; Lin Zhuang; Daming Chen; Xinghua Liang (International Journal of Photoenergy)
In this work we prepared double-layer antireflection coatings (DARC) by using the SiO2/SiNx:H heterostructure design. SiO2 thin films were deposited by electron-beam evaporation on the conventional solar cell with SiNx:H single-layer antireflection coatings (SARC), while to avoid the coverage of SiO2 on the front side busbars, a steel mask was utilized as the shelter. The thickness of the SiNx:H as bottom layer was fixed at 80 nm, and the varied thicknesses of the SiO2 as top layer were 105 nm and 122 nm. The results show that the SiO2/SiNx:H DARC have a much lower reflectance and higher external quantum efficiency (EQE) in short wavelengths compared with the SiNx:H SARC. A higher energy conversion efficiency of 17.80% was obtained for solar cells with SiO2 (105 nm)/SiNx:H (80 nm) DARC, an absolute conversion efficiency increase of 0.32% compared with the conventional single SiNx:H-coated cells.